EVALUATION OF LATERAL CONDENSATION ENDODONTIC TECHNIQUE WITH 7/D11 SPREADER, FINGER SPREADERS AND AN ULTRASONIC ACTIVATED TIP - Francisco Ojeda; Miriam González; Jairo Mariel; Francisco Gutierrez; Daniel Silva-Herzog; Ricardo Oliva (European Scientific Journal, ESJ, 2014)
The aim of this study was to compare the apical sealing ability,evaluating dye penetration in root canals filled with lateral condensationtechnique with the use of a 7/D11 spreader, a finger-spreader and anultrasonic activated tip. 90 distal roots of mandibular first molars wererandomly divided into three groups, each with 30 roots. Additionally wereused 4 roots as positive control and 4 as negative control. The preparedcanals were obturated with lateral condensation technique with sealer andgutta-percha cones condensed with 7/D11 in group 1, finger-spreader ingroup 2 and a tip activated by ultrasound in group 3. The samples wereimmersed in India ink and subsequently submitted to a demineralization andclearing process. The extent of dye penetration was measured using astereomicroscope with software Motic Images Advanced 3.0. The lowestmean leakage values were observed for 7/D11 group and the highest wereobserved for the ultrasound group. The difference between 7/D11 by oneside and finger spreader and ultrasound on the other was statisticallysignificant (p <0.05). Between ultrasonic tip and finger spreader groups thedifference was not significant.Under the conditions of this study it can be concluded that the use of the7/D11 instrument during condensation of gutta-percha showed better sealingability by allowing less leakage of the dye between the interphaseguttapercha-dentin than finger spreader and the ultrasonic tip.